A preliminary study on understanding and attitude towards chemical labeling using Globally Harmonised System (GHS) for secondary level students in Terengganu / Sarifah Fauziah Syed Draman, Rusli Daik and Mohd Lazim Abdullah - Syed Draman, Sarifah Fauziah; Daik, Rusli; Abdullah, Mohd Lazim (2011)
Chemical substances can be handled safely if properties of the chemical substances are wholly understood and the chemicals are properly managed. Improper use of the chemicals can cause accidents. Limitation of knowledge and training seem to be the factors for the chemical accidents. In Malaysia students are exposed to handling of chemical substances as early as at primary level but they usually handle chemical substances themselves including hazardous substances at secondary level when they are involved in laboratory activities. Therefore, understanding on classification and labeling of chemicals amongst secondary level students is crucial. Globally Harmonized System (GHS) is chosen in this study because this system is expected to be adopted internationally, and will replace the relevant laws and regulations used in different countries worldwide. Methodology for this study is descriptive quantitative survey. Cluster probability sampling was used for secondary levels students in Terengganu. Results found show that the students of secondary levels cannot recognize chemical substance correctly by using GHS. Attitude towards the importance of chemical labeling is also being discussed. Positive attitude are needed for good behavior while handling chemical substances. Results of this study show that a few factors such as schools and teachers affect the students understanding towards chemical substances labeling. Therefore, it is suggested that the hazard communication based on GHS should be incorporated into chemistry curriculum for secondary schools.